Antibiotic use for febrile neutropaenia in children with cancer. Issue 5 (22nd April 2012) - Harwood, B; Pinnick, T; Kendall, D; Walker, DA; Alukar, S
Abstract : Objectives: To assess if the antibiotic regimens being instituted are according to the NUH febrile neutropaenia guideline. To determine if gentamicin levels are being taken appropriately and are within recommended limits. To assess if the Paediatric Early Warning Score (PEWS) or the C reactive protein (CRP) is able to distinguish at admission those children who are more likely to have an unfavourable outcome. To determine the percentage of children who receive antibiotics within 1h of presentation. Methods: Patients admitted to NUH with febrile neutropaenia between August and November 2010 were identified from clinical notes. PEWS data and CRP values were collected at admission, 24 and 48 h from nursing observation charts and the NUH results system (NotIS) respectively. Antibiotic levels were retrieved from NotIS. The door to antibiotic time was calculated from the admission time recorded on nursing admission notes and the time at which the first dose of antibiotic was documented on the drug chart. Results: Data were collected from 20 patients aged 1.3–16.6 years (median 9.4 years). 13 patients (65%) were started on first line antibiotics in line with the NUH febrile neutropaenia guideline. Two patients were incorrectly given gentamicin as they were receiving nephrotoxic chemotherapy regimens. Gentamicin levels were available for 17 patients. 14 patients (82%) had levels taken correctly of which eight patients (57%) were within the specified range and 5 (36%) had low post dose levels. Median PEWS scores was 4 (20 patients) and CRP was reported on admission for eight patients (mean 10). Five patients had positive blood cultures but none were admitted to intensive care or died. The door to antibiotic time was determined in 11 patients and was less than 1 h in five patients (45%, mean 94 min). Conclusions: The majority of patients received first line antibiotics in accordance with the NUH febrile neutropaenia guideline. Since this review was completed the Trust has switched to once daily dosing of gentamicin and there has been a new guideline publicised. As a consequence of this change it is imperative that pre dose levels are measured correctly but post dose levels are no longer required. This review did not demonstrate any correlation between CRP or PEWS score and positive blood cultures or length of stay however larger studies are needed to investigate this further. In nearly half of patients the door to antibiotic time could not be determined from the medical or nursing notes. This highlights the need for a more robust system to be in place to record the time that patients present to hospital.